Some methods of improving freight transportation in short hauls - Bagdonienė, Danutė (Transport, 2003)
The results obtained in the investigation aimed to improve the transportation of commercial freight for short hauls in the city are presented. The performed tasks included the statistical analysis of freight flows; the forecast of the freight flows; a synthesis of a topological stmcture of the urban system of freight transportation and the description of the optimal structure of the truck stock. The conclusions have also been drawn and some recommendations provided.First Published Online: 19 Dec 2011